GAMBARAN STATUS GIZI REMAJA PELAJAR SEKOLAH MENENGAH PERTAMA/SEDERAJAT DI KOTA SIBOLGA: The Nutritional Status Description of Adolescent Junior High School Students in Sibolga City - Bibi Ahmad Chahyanto; Rita Sasmita; Verawaty Lumban Tobing (Forind Press, 2024)
Conducting anthropometric assessments to evaluate the nutritional status of adolescents represents a relatively straightforward and cost-effective approach for early detection of nutritional concerns. One of the health programs integrated with anthropometric measurements in adolescents is the health screening program and periodic examinations of school-age children and adolescents. This study aims to describe the nutritional status of adolescent junior high school students located in Sibolga City. This descriptive research used a cross-sectional study design through secondary data from the health screening results of new students in class VII of junior high school/equivalent in the 2018/2019 academic year. Further data processing and analysis were carried out from January to July 2023. The amount of data that had fulfilled the research inclusion criteria and was further processed to 1,550 respondents. Univariate analysis was employed to describe the description of the frequency and percentage values of each variable. The findings indicated that most respondents were 10-12 years old (78,06%) and attended public schools (68,32%). The proportion of male gender at 50,32% was almost equal to that of female at 49,68% and most respondents had good nutritional status (69,55%). The prevalence of respondents with poor nutritional status was 2,26%, undernutrition 7,23%, overnutrition 14,77%, and obesity 6,19%. The researcher expects that there will be further research related to the incidence of overnutrition problems in adolescents and the factors that influence its situation in Sibolga City.